Absorption in Sport: A Cross-Validation Study - Koehn, Stefan; Stavrou, Nektarios A. M.; Cogley, Jeremy; Morris, Tony; Mosek, Erez; Watt, Anthony P. (Frontiers in Psychology, 2017)
Absorption has been identified as readiness for experiences of deep involvement in the task. Conceptually, absorption is a key psychological construct, incorporating experiential, cognitive, and motivational components. Although, no operationalization of the construct has been provided to facilitate research in this area, the purpose of this research was the development and examination of the psychometric properties of a sport-specific measure of absorption that evolved from the use of the modified Tellegen Absorption Scale (MODTAS; Jamieson, 2005) in mainstream psychology. The study aimed to provide evidence of the psychometric properties, reliability, and validity of the Measure of Absorption in Sport Contexts (MASC). The psychometric examination included a calibration sample from Scotland and a cross-validation sample from Australia using a cross-sectional design. The item pool was developed based on existing items from the modified Tellegen Absorption Scale (Jamieson, 2005). The MODTAS items were reworded and translated into a sport context. The Scottish sample consisted of 292 participants and the Australian sample of 314 participants. Congeneric model testing and confirmatory factor analysis for both samples and multi-group invariance testing across samples was used. In the cross-validation sample the MASC subscales showed acceptable internal consistency and construct reliability (≥ .70). Excellent fit indices were found for the final 18-item, 6-factor measure in the cross-validation sample, χ2(120) = 197.486, p < .001; CFI = .957; TLI = .945; RMSEA = .045; SRMR = .044. Multi-group invariance testing revealed no differences in item meaning, except for two items. The MASC and the Dispositional Flow Scale-2 showed moderate-to-strong positive correlations in both samples, r = .38, p < .001 and r = .42, p < .001, supporting the external validity of the MASC. This article provides initial evidence in support of the psychometric properties, reliability, and validity of the sport-specific measure of absorption. The MASC provides rich research opportunities in sport psychology that can enhance the theoretical understanding between absorption and related constructs and facilitate future intervention studies.